2019
DOI: 10.1182/blood-2018-05-851667
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of SOX11 expression through CCND1 and STAT3 in mantle cell lymphoma

Abstract: The neural transcription factor SOX11 is usually highly expressed in typical mantle cell lymphoma (MCL), but it is absent in the more indolent form of MCL. Despite being an important diagnostic marker for this hard-to-treat malignancy, the mechanisms of aberrant SOX11 expression are largely unknown. Herein, we describe 2 modes of SOX11 regulation by the cell-cycle regulator cyclin D1 (CCND1) and the signal transducer and activator of transcription 3 (STAT3). We found that ectopic expression of CCND1 in multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…SOCS3, a negatively regulator of the JAK-STAT signaling pathway, loses its expression in~50% of MCL due to DNA methylation [90]. A recent study has revealed a unique role of STAT3 in MCL, which demonstrates that STAT3 represses expression of SOX11, a critical transcription factor that promotes lymphomagenesis in MCL [91]. This finding indicates that STAT3 may not be an ideal target in MCL given its negative role in SOX11 regulation.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%
“…SOCS3, a negatively regulator of the JAK-STAT signaling pathway, loses its expression in~50% of MCL due to DNA methylation [90]. A recent study has revealed a unique role of STAT3 in MCL, which demonstrates that STAT3 represses expression of SOX11, a critical transcription factor that promotes lymphomagenesis in MCL [91]. This finding indicates that STAT3 may not be an ideal target in MCL given its negative role in SOX11 regulation.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%
“…Sex determining region Y-related HMG-box 11 (SOX11) is a type of structurally-related transcription factor and belongs to group C of SOX family (17,18). SOX11 is critical for regulating organ development, particularly in the nervous system (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of low expression of SOX11 in HCC remains unclear. STAT3 is an oncogene, which can negatively regulate SOX11 expression [24]. After the use of STAT3 inhibitor, SOX11 expression levels were upregulated in mantle cell lymphoma [24].…”
Section: Discussionmentioning
confidence: 99%